Cytotoxic effect of the methanolic extract of three ecotypes of Lepidium peruvianum, Chacón on cellular lines HeLa and HT-29 - Alzamora, Libertad (2006)
The search of natural compound with cytotoxic and antitumoural activities is one of the current priorities of the fight against the cancer; being necessary to analyze new extracts of plants. The objective in this paper was to evaluate the cytotoxic activity of the methanolic extract (ME) of the black, purple and yellow ecotypes of Lepidium peruvianum, Chacón (at present Lepidium meyenii Walp.), Maca, on the cellular lines HeLa (Human Epithelial Carcinoma) and HT-29 (Human Colon Adenocarcinoma). For the cellular line HT-29, the inhibitory concentration of 50% of the cellular growth (IC50) with the black, purple and yellow ecotypes was of 8,32 mg/ml, 9,28 mg/ml and 0,487 mg/ml, respectively; while for the cellular line HeLa was of 2,4 mg/ml, 1,93 mg/ml and 0,66 mg/ml respectively. Additionally, ME of the yellow ecotype was evaluated with two years of storage (10ºC) determining an IC50 4,29 mg/ml for HT-29 and 4,17 mg/ml for HeLa. We concludes that the cytotoxic effect of the yellow ecotype on HT-29 and HeLa went high to the showed by the black and purple ecotypes; that the most sensitive cellular line to the yellow, black and purple ecotypes is HeLa, and that the ME of the yellow ecotype conserved its cytotoxic properties in spite of the time of storage.